Substantial consequences and factors leading towards construction project success and failure - V. Doraisamy, Sunitha; Akasah, Zainal Abidin (AENSI Publishing Corporation, 2015)
The phenomenon on the incompletion of construction projects in Malaysia is something very common at the moment. But to a more positive note, there are also successful projects which has been established in a large scale over the years. When there is an existence of such success, yet the project failures are yet to be apprehended as well. Whether the most appropriate measures have been taken in curbing this problem is yet to be sure off, looking at the existence of project failures. Therefore, this paper gives an outlook on the current situation of abandoned projects in Malaysia, and also takes a look on the factors on both success and failures of projects, where the essential information on this was obtained from statistics provided by Ministry of Housing and Local Government, and also based on the comparison matrix that was established from the causes identified by researches from other countries, including Malaysia itself. Some of the information that was able to gather from this was the types of causes with its ranking from the most to the least, and other underlying factors and driving keys on the successful completion of projects. The outlook on the failures and success of a project could be an absolute strategy that could be implemented in the effort towards restoration of abandoned projects in Malaysia, and in other countries as well which are also experiencing the same adverse situation.